Amerikaanse folk songs en protest songs [Bladmuziek] : tekstboekje bij een voordracht : oorspronkelijke tekst met Nederlandse vertaling - Verbeke, Hugo (Sint-Niklaas : Pro Manuscripto.)
Deze publicatie bevat volgende liederen
America is beautiful
My old Kentucky home
Swanee River
Battle Hymn of the Republic
John Brown's body
Down by the riverside
Keep your eyes on the prize
Christmas is coming
Ain't that a rockin'
Virgin Mary had a baby
The drunken sailor
Clementine
The farmer's curst wife
Four nights drunk
Blue Tail Fly
Oh Susanne
Black is the color
The trees they grow high
Queen of hearts
I'm a rambler
Kitty
Once I had a sweatsheart
Don't think twice
Lonesome raod
By the banks the Ohio
Frankie and Johnny
Jackeroe
Hard traveling
Black, brown and white
If yo miss me
Who killed Davey Moore
Masters of war
With God on my side
Little boxes
What did you learn at school
Blowin' the wind
It's a herd rain
Where have all the flowers gone
Healing river
We shall overcome
Nederlands
Engels
Bladmuziek
Keywords: liederen